2019
DOI: 10.2147/clep.s191437
|View full text |Cite
|
Sign up to set email alerts
|

<p>Health indicator recording in UK primary care electronic health records: key implications for handling missing data</p>

Abstract: Background Clinical databases are increasingly used for health research; many of them capture information on common health indicators including height, weight, blood pressure, cholesterol level, smoking status, and alcohol consumption. However, these are often not recorded on a regular basis; missing data are ubiquitous. We described the recording of health indicators in UK primary care and evaluated key implications for handling missing data. Methods We examined the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 37 publications
2
36
0
Order By: Relevance
“…For example, in clinical practice, younger women are more likely than younger men to have weight recorded when they consult their family physician (general practitioner). 12 In other words, the distribution of missing data in weight depends on the individual's sex, so weight is missing at random (MAR) given sex. The same will apply to other partially observed outcomes that are MAR.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in clinical practice, younger women are more likely than younger men to have weight recorded when they consult their family physician (general practitioner). 12 In other words, the distribution of missing data in weight depends on the individual's sex, so weight is missing at random (MAR) given sex. The same will apply to other partially observed outcomes that are MAR.…”
Section: Introductionmentioning
confidence: 99%
“…The study found less than half of people with dementia had a weight and/or BMI recorded, consistent with another THIN study reporting 47% had this recorded in 2010–2013, 25 and other reports of poor weight recording in primary care. 31 Eating and drinking difficulties are common in dementia. The risk of malnutrition increases as dementia progresses and people with dementia have 10 times more malnutrition or dehydration-related hospital admissions compared with age-matched controls.…”
Section: Discussionmentioning
confidence: 99%
“…This contrasts with studies set in birth cohorts, teratology information services, or general practice databases, which often have to contend with much higher levels of missingness and with patterns that are likely to be informative. The substantial problem of missing data in these study types has promoted important methodological research on the topic, 23,24 as well as a greater uptake of multiple imputation methods by researchers using this type of data (Table I). Simpler approaches to handle missing data such as indicator variables were often not reported in the articles we evaluated, which is encouraging given the well-established shortcomings of the method.…”
Section: Methods To Handle Missing Datamentioning
confidence: 99%